Providing a guaranteed power for the BTS in telecom tower based on improved balanced owl search algorithm - Daming Li; Lianbing Deng; Qinglang Su; Yong-Hua Song (Energy Reports, 2020)
The telecommunication industry is the technology of communication among humankind. One problem for this industry is to provide the required energy for its towers in the remote rural areas in the absence of the grid. This objection causes dependency of this industry to the diesel generators and battery banks as backup resources. Despite not being resilient and the effect of environment for the power supplies in diesel generators is still widespread. This paper presents a new optimized and environmentalist power supply configuration for the telecommunication tower based on the proton exchange membrane fuel cell (PEMFC). An optimized PI-based converter is also utilized to keep the source value reliable. For achieving optimized results for the PI controller, a developed version of the owl search algorithm is proposed. Simulation results have been applied in different conditions and the results are compared with Ziegler-Nichols, particle swarm optimization algorithm, and emperor penguins optimizer based PI controller to show the excellence of the proposed method.
Keywords: 330; Improved; Owl search algorithm; Boost converter; DC distribution; PEMFC; Telecom tower; Voltage regulation